Presença do Papilomavírus Humano (HPV) em leucoplasia e carcinoma epidermoide de boca e sua relação com marcadores de proliferação e diferenciação celular - Vasconcelos, Simone Bertozi de Souza (2021)
The characterization of human papillomavirus (HPV) as the etiologic agent of leukoplakia and carcinoma of the oral cavity is still controversial, although its involvement in oropharyngeal cancer has already been identified. These lesions in the oral cavity have risk factors in common, with the possibility that HPV infection may favor the malignant transformation of leukoplakia progressing to oral squamous cell carcinoma (OEC). This work aimed to identify, through molecular biology methods, the presence of HPV in leukoplakia and carcinoma, as well as its relationship with the expression of p16, p21, ki67 and CK14 and CK19 related to the cell cycle, in its cell proliferation and differentiation. For detection of HPV-DNA by Polymerase Chain Reaction (PCR), samples of exfoliated cells from the surface of the lesions and from other regions of the oral mucosa without alterations in patients treated at the Clinics of the Faculty of Dentistry of the Federal University of Mato Grosso do Sul and the Center for Dental Specialties from the Municipality of Campo Grando from September 2018 to November 2020, clinically classified as oral leukoplakia (n=22) and oral squamous cell carcinoma (n=15). Lesions samples were obtained by biopsy and embedded in paraffin and divided into groups according to the absence or presence of dysplasia or neoplasia in the histopathological evaluation. To identify the expression of p16, p21, Ki67, CK14 and CK19, the blocks were analyzed using a simple immunohistochemical technique. The frequency of HPV detection was 27% of patients who participated in the survey. There was no statistical difference regarding the increase in the expression of p16 (p=0,093) and Ki67 (p=0,169) between the types of lesions studied. A statistical difference was observed in the expression of CK19 and p21 (p<0.001) between the groups of evaluated lesions and in the moderate diffuse expression of CK14 (p=0.015), which was significantly lower in leukoplakia without dysplasia. When comparing positive and negative samples for HPV, there was only an increase in ki67 expression with a significant difference (p<0.001) in samples positive for HPV. The increased expression of the studied markers seems to be related to the degree of dysplasia or malignancy of the lesions, with the exception of p16 expression, which was not related to malignancy or the presence of viral DNA. The presence of HPV associated with increased expression of ki67 indicates viral interference in the proliferative capacity of the oral epithelium.